2016
DOI: 10.1002/jbio.201500341
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Raman and fluorescence lifetime spectroscopy from human atherosclerotic lesions using a bimodal probe

Abstract: Fluorescence lifetime imaging (FLIm) and Raman spectroscopy are two promising methods to support morphological intravascular imaging techniques with chemical contrast. Both approaches are complementary and may also be used in combination with OCT / IVUS to add chemical specificity to these morphologic intravascular imaging modalities. In this contribution, both modalities were simultaneously acquired from two human coronary specimens using a bimodal probe. A previously trained SVM model was used to interpret t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Optical techniques are often focused on investigating the composition and vulnerability of plaques (20)(21)(22). But for the characterization of early plaque development, the cellular level of lipid metabolism is also of foremost interest.…”
mentioning
confidence: 99%
“…Optical techniques are often focused on investigating the composition and vulnerability of plaques (20)(21)(22). But for the characterization of early plaque development, the cellular level of lipid metabolism is also of foremost interest.…”
mentioning
confidence: 99%
“…The advantage of combining these imaging modalities is to complement FLIM, an intravascular surface imaging technique, with high molecular specificity data from Raman, which is able to distinguish between calcifications, cholesterol, or carotenoids. The study also suggested that this bimodal probe can be combined with OCT/IVUS, adding chemical specificity to these morphologic intravascular imaging methods [91]. The recent animal study also indicated potential applications of combined OCT-Raman spectroscopy technique for chemical analysis of plaque lipid depositions, including triglycerides as the major component [92].…”
Section: Multimodality Imagingmentioning
confidence: 93%
“…Moreover, the employment of Raman spectroscopy-FLIM bimodal probe demonstrated high chemical specificity in detecting plaque components in human coronary specimens [91]. The advantage of combining these imaging modalities is to complement FLIM, an intravascular surface imaging technique, with high molecular specificity data from Raman, which is able to distinguish between calcifications, cholesterol, or carotenoids.…”
Section: Multimodality Imagingmentioning
confidence: 99%
“…Both modalities were simultaneously acquired from two human coronary specimens using a bimodal probe. 135 Raman spectroscopy could distinguish lipid from necrotic cores, whereas FLIM extracted information could identify fibrous caps.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%